Pasteurisation of Soursop (Annona Muricata L.) Puree and its Effects on Physico-Chemical Properties - Ara, Umme (2000)
A study was carried out to process soursop puree. The study includes, the establishment of optimum conditions of temperature and time for pasteurisation; shelf life study using different packaging and storage temperature combinations; characterisation and ultrastructural identification of puree and juice cloud at two processing and storage conditions; and characterisation of pectin-protein particulate in the juice cloud. Physico-chemical evaluation of freshly extracted soursop pulp showed high pectin esterase (PE) actMty (32.1 unit/g) and vitamin C content (21 mg/100g). The pH was low (3.7) and the acidity was high (1.02%). These properties were considered advantageous for pasteurisation. A Response surface methodology was used to determine optimum pasteurisation conditions for inactivation of PE with maximum ascorbic acid retention. The results showed that the optimum pasteurisation condition was at 79°C for 69 sec, with predicted nil PE activity and ascorbic acid content of 5.88 mg/100g. The storage stability of the puree was evaluated for 12 weeks and the parameters examined were microbial count (total plate count, yeast & mould, and E. coli), PE activity, cloud stability, colour, viscosity, pH, titratable acidity, °Brix, ascorbic acid and sugar content, as well as sensory properties. The packaging materials used were laminated aluminium foil, general purpose lacquered can and polypropylene bottles and the samples were stored at ambient temperature (28-37°C), 15°C, 4°C, and -20°C. It was observed that natural soursop puree pasteurised at the established optimum conditions of 79°C for 69 sec completely inactivated the PE and stabilised the cloud in juice without affecting nutrients and sensory quality. Samples packed in laminated aluminium foils and stored at 4°C was most stable during the storage period of 12 weeks. It showed decreased loss in cloud, viscosity, colour, nutrient, and lowest microbial growth. Effect of processing and storage studies showed that the puree prepared by maceration process was low in pulp sediment and high in cloud content. Viscosity, °Brix, pulp volume and cloud stability were affected by freezing damage of cloud particles. Scanning electron micrograph of fresh and pasteurised juice cloud showed a continuous matrix of protein filaments. On the other hand, similar observation made on frozen juice cloud showed shrinked protein filaments and collapsed network. This suggest that there was a loss in consistency and cloud due to freezing. The cloud of single strength soursop juice was white, fine, cottony textured and Constituted about 0.103% of the dry solid. The cloud composed of 35.5% protein, 22.5% carbohydrate, 14.3% lipid and 0.64% polyphenol content and a density of 1.08 g/ml. Transmission electron micrograph of stable juice revealed that the cloud particles ranged in size from 0.13µm - 3.0µm and showed an obvious close association of protein-lipid and protein-pectin. Flocculates of insoluble pectates and aggregated particles formed by enzymatic action were evident in unpasteurised juice cloud. Soursop juice cloud contained an average of 10.36% total pectin of which 66.3% soluble pectin, 11% inherently insoluble pectin and 24.4% protopectin. From the 35.5% total cloud protein, 48.7% was inherently insoluble protein, 38.6% complexed with other polymeric constituent and 13% complexed with low molecular weight cloud constituents.